2007
DOI: 10.1159/000102959
|View full text |Cite
|
Sign up to set email alerts
|

Acute Pancreatitis in the Guangdong Province, China

Abstract: Background/Aims: Many studies have recently been published on acute pancreatitis; however, few large-sample studies have been focused on the risk factors for deaths in severe acute pancreatitis. To address this issue, the present study was intended to assess etiology, severity, and mortality of acute pancreatitis in the Guangdong Province (Guangdong), China, and to analyze the risk factors responsible for deaths in severe acute pancreatitis in this large series of patients. Methods: Four tertiary medical cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 34 publications
3
7
1
Order By: Relevance
“…The etiology of AP in this study was comparable with that in other studies from Asia [12, 13], with the leading causes of AP being gallstones and alcohol-related disease. However, gallstones were more prevalent in female, while alcohol was so in male, of which were well known.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The etiology of AP in this study was comparable with that in other studies from Asia [12, 13], with the leading causes of AP being gallstones and alcohol-related disease. However, gallstones were more prevalent in female, while alcohol was so in male, of which were well known.…”
Section: Discussionsupporting
confidence: 88%
“…The age and sex of the patients with AP in this study were very similar to those of patients in recent studies from the West [11] and Japan [12]; however, the mean age was slightly higher than that in a study from China [13, 14]. The typical clinical presentation was abdominal pain in almost all patients.…”
Section: Discussionsupporting
confidence: 81%
“…The natural course of SAP progresses in two phases: Comorbid systemic inflammatory response syndrome (SIRS) and multiple organ dysfunction syndrome (MODS) due to the release of a large amount of cytokine in the early phase, and infection of pancreatic necrosis and secondary MODS in the late phase. Both contribute to considerable morbidity/mortality varying from 7% to 42% 3–6 . Tsui in his study indicated that the mortality of SAP in Nankai hospital was 9.23% between January 2000 and April 2008 7 …”
Section: Introductionmentioning
confidence: 96%
“…Both contribute to considerable morbidity/mortality varying from 7% to 42%. [3][4][5][6] Tsui in his study indicated that the mortality of SAP in Nankai hospital was 9.23% between January 2000 and April 2008. 7 There are a number of scoring systems to assess the severity of AP.…”
Section: Introductionmentioning
confidence: 99%
“…It is a common disease (current UK incidence: 150–420 cases per million per annum) and increasingly prevalent. 1 However, despite recent improvements in intensive care unit management and techniques of organ support, the severity and mortality associated with AP has not decreased since the 1970s 1 : up to 25% of patients will be diagnosed with severe disease 25 and approximately 4% of all patients will die. 6,7 This can be partly explained by the fact that no specific prophylactic or therapeutic agent is available, and current management is largely supportive.…”
Section: Introductionmentioning
confidence: 99%